Workplace stress from actual and desired computer-mediated communication use: a multi-method study - Jean-Francois Stich; Monideepa Tarafdar; Cary L. Cooper; Patrick Stacey (2017)
The use of computer-mediated communication applications can lead to workplace stress for employees. However, such stress is influenced not only by how individuals actually use computer-mediated communication applications, but also how they desire to use them. This paper examines how the individual’s actual and desired use of communication tools together influence his or her workplace stress. It does so across a range of computer-mediated media (e.g. email or instant messaging), and workplace stressors (e.g. workload or work relationships). This investigation is conducted using a multi-method research design. The quantitative study found that desired and actual use together influenced workplace stress, mostly for email, but not for other media. The qualitative study further showed that such influence depends on organizational conditions such as available media or co-workers preferences. The findings emphasize the importance of considering the individuals’ desired use of CMC media, and their subjective appraisals of different media.